PROPOSED MARKETING STRATEGY FOR INCREASING CUSTOMER ENGAGEMENT (CASE : MIETHY.ID - HEALTHY NOODLE) - Iftinaan Landau, Mudhiiah
The increase in the use of social media has caused many influencers to invite people to adopt a healthy lifestyle. This encourages increased public awareness of a healthy lifestyle, making the healthy food industry continue to grow. However, if you want to move into the healthy food industry with a special concentration, Miethy needs to increase brand awareness to be trusted and known by the public. Miethy is a new brand engaged in the healthy food industry, which is not yet known by the public. Miethy sells products that are much healthier than the noodles on the market due to the high quality of raw materials with many benefits. With the advantages of this product, it is hoped that Miethy can attract public trust and interest to become the top of mind of healthy food. The method used is a problem-solving research method using primary and secondary data. The analysis used is branding, internal and external analysis consisting of 4p, STP, five porter's forces, and competitor analysis. The analysis carried out helps to create a SWOT value of the company, hopefully can find the problems and solution that Miethy needed. Internal and external analysis revealed several main problems faced by Miethy, including brand awareness that has not yet been attached to consumers' minds, less effective promotions, and competition in the healthy food industry. In this study, there is limited literature so that if it is to be applied in other industries,additional literature and more in-depth research are needed. The author conducted an in-depth analysis using various problem-solving tools, and from the analysis, the authors obtained following results. Brand image and brand awareness of Miethy are not firm yet, so that Miethy products are not yet known by the general public. Furthermore, in the 4p analysis, it was found that Miethy products do not have a marketing permit in force in Indonesia, sales are still low, considered expensive, the promotion process has not been maximized, and the public does not yet know our products. Furthermore, the five porter's forces show that the Miethy market is relatively easy to enter, so it is quite competitive in that market. Moreover, the last is competitor analysis which concludes that when compared to its competitors, Miethy has a few product variants. Based on the results of this study, Miethy needs to increase promotional activities which are divided into several action plans, namely collaborating with partners and influencers, participating in healthy food bazaars or events, creating or sponsoring health seminars, providing free samples, improving social media and adding and maximizing place to sell. Next is to make a new product variant, namely healthy mie snack which has three variants, namely chicken curry, cheese and spicy, which is expected to make Miethy able to compete with similar competitors. Moreover, the last in an effort to increase trust in Miethy, namely by making a BPOM permit and registering an halal certificate. After making the changes that have been discussed in this report, Miethy can increase brand awareness and brand image in the eyes of consumers